Natural history of mesenteric venous thrombosis in patients treated with vitamin K antagonists - Dentali, Francesco; Ageno, Walter; Witt, Dan; Malato, Alessandra; Clark, Nathan; Garcia, David; McCool, Kathleen; Siragusa, Sergio; Dyke, Shannon; Crowther, Mark; for the WARPED consortium (Thrombosis and Haemostasis, 2009)
Knowledge on the natural history of mesenteric vein thrombosis (MVT) and of the efficacy and safety of long-term oral anticoagulant therapy (OAT) in this setting is based on small uncontrolled series of patients with a limited follow-up. It was the aim of the study to assess the natural history of MVT in a cohort of patients treated with OAT. The charts of all MVT patients currently attending or who have attended four anticoagulation clinics were reviewed. Information on risk factors, treatment, recurrence, major bleeding and mortality was collected. Seventyseven patients (mean age 49.2 years; 45 males) were included with a median follow-up of 36 months (range 2–204 months). Forty-six patients were treated with long-term OAT. Seven patients had venous thromboembolism (VTE) recurrence (5 splanchnic vein thromboses and two pulmonary emboli) for an incidence rate of 23.4 events /1,000 year patients. In two patients recurrentVTE occurred during OAT, for an incidence rate of 10.5 events /1,000 year patient. Five patients had VTE recurrence when OAT was suspened for an incidence rate of 45.9 events /1,000 year patient. Two patients (2.6%) had a major bleeding event. 97.3% of patients were alive at one year, and seven patients (9.1%) died during follow up. In conclusion, patients with MTV seem to have a low risk of recurrentVTE while receiving OAT. This risk appears increased after treatment is stopped.
Keywords: Mesenteric vein thrombosis; oral anticoagulant